Quality of life of patients receiving a single or combination of calcium channel blocker-angiotensin receptor blocker: A cross-sectional study in West Java, Indonesia - Juwita Ramadhani, Mutakin Mutakin, Dyah Aryani Perwitasari, Jutti Levita (Journal of Applied Pharmaceutical Science, 2020)
The prevalence of hypertension, based on the Indonesian Basic Health Research 2018, was 34.1%. Hypertensive patients usually show a low quality of life (QoL) due to their lifelong drug dependence. This cross-sectional study was conducted to determine the QoL of adult hypertensive patients treated with a single calcium channel blocker (CCB) and combination of CCB and angiotensin receptor blocker (ARB) at a primary referral hospital in West Java during December 2018–February 2019. The QoL of the patients was determined using the Indonesian validated Euroqol 5 dimensions 5 level and Euroqol visual analog scale questionnaires. 83 adult hypertensive outpatients were recruited and agreed to participate in this study. Of the 83 hypertensive patients, 44.6% were being treated with a single CCB and 55.4% were being given the combination of CCB and ARB. The characteristics of the patients were as follows: the age was 51 ± 1.04 years, 71.3% were female, 84.3% were married, 66.2% never undertook physical activity, daily drugs consumed 4 ± 0.19 items, and the duration of hypertensive therapy was 20 ± 3.3 months. Most of the patients indicated problems in the area of pain and anxiety. The hypertensive patients treated with a combination of nifedipine and candesartan indicated the best QoL, whereas the lowest QoL was found in patients treated with a combination of nifedipine and valsartan.
Keywords: Angiotensin receptor blocker, calcium channel blocker, hypertension, quality of life.